2008
DOI: 10.1016/j.jvs.2008.10.050
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cardiac Outcome in High-Risk Patients Undergoing Elective Endovascular or Open Infrarenal Abdominal Aortic Aneurysm Repair

Abstract: Objective: To examine and compare existing pre-operative risk prediction methods for elective abdominal aortic aneurysm (AAA) repair.Design: Systematic review. Methods: Medline, EMBASE and the Cochrane library were searched for articles that related to risk prediction models used for elective AAA repair.Results: 680 abstracts were reviewed and after exclusions 28 articles encompassing 10 risk models were identified. The most frequently studied of these were the Glasgow Aneurysm Score (GAS), the Physiological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 0 publications
2
12
0
1
Order By: Relevance
“…All reported a lower mortality rate in patients taking a statin following AAA repair. Two studies found this difference to be significant by 1 year22, 23. All studies found the effect to be significant at 2 and 5 years.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…All reported a lower mortality rate in patients taking a statin following AAA repair. Two studies found this difference to be significant by 1 year22, 23. All studies found the effect to be significant at 2 and 5 years.…”
Section: Resultsmentioning
confidence: 93%
“…Eleven of the 12 studies were retrospective cohort studies5–7, 19–26; one was a prospective cohort study27. Table S1 (supporting information) summarizes study characteristics.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations